Improving Sleep in Young Children - Rodriguez, Marie (East Carolina University)
Sleep disorders are a serious problem in the United States alone, affecting between 50 and 70 million individuals. Between 20% and 30% of toddlers, infants and preschoolers around the world suffer from problems with falling asleep or staying asleep throughout the night. One of the most common sleep problems in young children is delayed sleep onset (DSO). This occurs when the child has difficulty going to bed within 20 minutes. Night waking episodes, when the child wakes up at least once per night and does not reinitiate sleep independently, are another common problem. DSO and night waking episodes in children can negatively impact caregiver sleep as well. Because these children lack the ability to self-soothe, their caregiver(s) have to wake up and help them fall back to sleep. One evidence-based intervention for DSO is letting the child "cry it out", also called "extinction". However, some caregivers are not comfortable with this method. Other interventions include moving the child's bedtime back by small increments until the child's desired bedtime is reached, called fading. Fading interventions have been effective when paired with response cost, but this has only been studied in the case of one typically developing child. This pilot study tested a novel fading intervention for typically developing children between the ages of two and six. During the intervention, caregivers moved the child's bedtime back by 15 minutes every night and woke them at the same time every morning. Sleep was monitored using ActiGraphs to objectively examine frequency of night waking episodes and how well the intervention worked over 3.5 to 6.5 weeks. By implementing this pilot study of sleep, I aimed to determine the feasibility, acceptability, and preliminary effectiveness of a sleep intervention in promoting independent sleep onset (ISO) and less frequent night waking episodes in typically developing preschool aged children with DSO. While the two caregivers who completed this intervention demonstrated that it was feasible for some, it was not feasible for the 12 caregivers who declined to participate in either part or all parts of the study. The two caregivers who completed this intervention found it to be acceptable. The intervention was also effective at reducing night waking episodes in both participants. For one participant, diaries revealed night waking episodes were reduced from five episodes during baseline (an average of one episode per night) to zero at intervention and post-intervention. For the other participant, the sleep diary revealed eight night waking episodes during baseline, three episodes during the intervention, and the caregiver reported qualitatively that night waking episodes had ceased altogether post-intervention (the caregiver did not fill out diaries during post-intervention). The intervention was also effective at promoting ISO, which was found to continue past the post-intervention phase based on a follow up email survey for both participants. Both caregivers reported a decrease in the length of time it took their child to fall asleep independently from 30 minutes at baseline to 15 minutes at post-intervention. Limitations of this study included a small sample size, homogeneity of participants, unforeseen barriers to approval of the study, including difficulties with recruitment due to the COVID-19 pandemic, and multiple barriers to participants completing the study as written in the protocol. Future studies of sleep should include larger, more diverse samples, seek to reduce caregiver barriers to participation, and increase feasibility of sleep interventions for night waking and delayed sleep onset.
Keywords: independent sleep onset; night waking; bedtime fading; Sleep disorders in children--United States; Child psychology--United States; Sleep--Stages; Sleep--Psychological aspects